AB0257 Genetic effects of HLA-DRB1, IL4R, and FCΓRIIB on long-term treatment responses in patients with early rheumatoid arthritis: 78-week results of optima. (23rd January 2014) - Skapenko, A.; Smolen, J.S.; Kavanaugh, A.; Santra, S.; Kupper, H.; Schulze-Koops, H.
Abstract : Background: Previous analyses suggested that the HLA-DRB1 shared epitope (SE), and the IL4R V50I and the FcγRIIb I232T single nucleotide polymorphisms (SNPs) affected response to adalimumab (ADA) plus methotrexate (MTX) 1 . Their effect on long-term responses is unclear. Objectives: To examine 78-wk clinical responses according to 3 candidate loci: HLA-DRB1 SE, and IL4R I50V and FcγRIIb I232T SNPs. Methods: MTX-naïve patients (pts) ≥18 yr with RA <1 yr, active disease [DAS28 (CRP)>3.2, ESR≥28 mm/hr or CRP≥1.5 mg/dL], and >1 erosion, RF+, or anti-CCP+ were randomized to ADA+MTX or placebo (PBO)+MTX for 26 wks (Period 1, P1). Pts who achieved a stable LDA target (DAS28<3.2 at wks 22 & 26) with ADA+MTX were re-randomized to continue ADA+MTX or have ADA blindly withdrawn for 52 wks (P2). Pts who achieved the target with PBO+MTX continued blinded therapy. Pts who did not achieve the target were offered open-label (OL) ADA+MTX. Results: Baseline demographics were similar across alleles. The table shows the percentage of pts achieving DAS28<3.2 at wk 78. There were no consistent patterns for the IL4R alleles in any group. While limited by small sample sizes, pts with FcγRIIb-CC appeared to have higher responses at wk 78 among groups initially exposed to ADA+MTX during P1. The positive influence of SE was apparent at wk 78 in groups originally exposed to ADA+MTX, particularly in pts who did not achieve the stable LDA target at wks 22 & 26 but continued ADA+MTX. However, this pattern was not observed in pts who failed to achieve the target with MTX and were subsequently treated with ADA+MTX. The interaction between SE and IL4R observed during P1 was not apparent in long-term responses to ADA+MTX. Conclusions: Regardless of genetic background, wk 78 responses were generally higher for pts who achieved the stable LDA target at wks 22 & 26. The positive effects of HLA-DRB1 SE and FcγRIIb-CC in response to ADA+MTX previously noted at wk 26 were less apparent at wk 78, but noticeable in pts who failed to achieve the target. Further, while SE predicted clinical response to ADA+MTX, particularly when combined with IL4R alleles, it had no influence on the ability to withdraw ADA in pts who achieved LDA. These findings may indicate that genetic factors have a stronger influence on initial treatment response than on sustained disease control. References: Skapenko et al. EULAR 2011 #THU0309. Disclosure of Interest: A. Skapenko: None Declared, J. Smolen Grant/Research support from: Abbott, Amgen, Astra-Zeneca, BMS, Celgene Centocor-Janssen, Glaxo, Lilly, Pfizer (Wyeth), MSD (Schering-Plough), Novo-Nordisk, Roche, Sandoz, UCB, Consultant for: Abbott, Amgen, Astra-Zeneca, BMS, Celgene Centocor-Janssen, Glaxo, Lilly, Pfizer (Wyeth), MSD (Schering-Plough), Novo-Nordisk, Roche, Sandoz, UCB, A. Kavanaugh Grant/Research support from: Abbott, Amgen, Astra-Zeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, Consultant for: Abbott, Amgen, Astra-Zeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, S. Santra Shareholder of: Abbott, Employee of: Abbott, H. Kupper Shareholder of: Abbott, Employee of: Abbott, H. Schulze-Koops Consultant for: Abbott